Congenital Horner and Scimitar syndrome in a newborn: a previously unreported combination. Issue 11 (30th November 2020) - Carvalho, Joana; Maia, Mariana; Mota, Ágata; Martins, Teresa
Abstract : Here we report a case of a term newborn presenting with left palpebral ptosis, anisocoria and heterochromia as well as cleft palate and heart murmur. Congenital Horner syndrome was suspected and a thoracoabdominal CT scan was performed to rule out neuroblastoma. This revealed an anomalous drainage of right pulmonary veins to a collector that drains to the inferior vena cava, leading to the diagnosis of Scimitar syndrome. Echocardiogram showed an ostium secundum atrial septal defect, enlarged right chambers and a dilated coronary sinus due to a persistent left superior vena cava. The combination of Horner and Scimitar syndrome has never been described before. This case should encourage clinicians to use a multidisciplinary approach in order to guarantee an adequate diagnosis and management.